Efficacy of some plant leaf extracts against weed fungi coming up during cultivation of oyster mushroom on sugarcane bagasse - SINGH*, A.K. (Indian Phytopathology, 2002)
Leaf extracts from 10 plants were tested for their efficacy against fungal contaminants (mainly Aspergillus flavus, A. niger and Penicillium citrinum) occurring during Pleurotus florida cultivation. Extract of Hyptis suaveolens gave the best fungalcontrol followed by extracts from Adenocalymma alleces and Aegle marmelos.